Predicting invasions of nonindigenous plants and plant pests (National Academy Press, 2002)
Nonindigenous plants and plant pests that find their way to the United States and become invasive can often cause problems. They cost more than $100 billion per year in crop and timber losses plus the expense of herbicides and pesticides. And this figure does not include the costs of invasions in less intensively managed ecosystems such as wetlands. Nonindigenous Plants and Plant Pests examines this growing problem and offers recommendations for enhancing the science base in this field, improving our detection of potential invaders, and refining our ability to predict their impact. The book analyzes the factors that shape an invader's progress through four stages: arriving through one of many possible ports of entry, reaching a threshold of survival, thriving through proliferation and geographic spread, and ultimate impact on the organism's new environment. The book also reviews approaches to predicting whether a species will become an invader as well as the more complex challenge of predicting and measuring its impact on the environment, a process involving value judgments and risk assessment. This detailed analysis will be of interest to policymakers, plant scientists, agricultural producers, environmentalists, and public agencies concerned with invasive plant and plant pest species.